The double tragedy of irrigation systems in Tamil Nadu, India: assessment of the replacement of traditional systems by private wells - Kajisa, Kei (IWA Publishing, 2012)
This paper investigates the impact of the replacement of traditional communal irrigation systems called tanks by modern irrigation systems, that is, private wells with pumps, using a village and household data set collected in Tamil Nadu, India. Our statistical analyses find that, once the tanks deteriorate, the rice yield of farmers who have no access to wells and thus rely solely on traditional irrigation systems will decrease, whereas those of farmers with well access will not be affected. Since compensation for yield loss by income diversification is difficult, the reduction of income is so large that poverty among farmers without well access increases. Our analyses also find that, even among farmers with well access, the dissemination of private wells results in no significant increase in net return or profit of rice cultivation, presumably because the overexploitation of groundwater increases the cost of irrigation and cancels out the well users' high revenue from high yield. In this way, the replacement process creates a double tragedy: increased poverty among farmers without well access and overexploitation and profit reduction among farmers with well access. Policy options to avoid the tragedy are discussed in the concluding section.